(3GdeTQhYjI GdehVhYjI ddfXGe GdbGfhfi GdeUQi GdeYGUQ ai VhA GdeGOI GdKGfjI ef GdOSJhQ GdMGdi (B/ s - (3NGdO YHOGdYXje ESeGYjds; (3eMehO YR GdYQH GdSbGs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2018)
(3JfGhdJ GdQSGdI GdeTQhYjI GdehVhYjI ddfXGe GdbGfhfi GdeUQi ai VhA GdeGOI GdKGfjI ef GdOSJhQ(B. (3GSJNOe GdHGMK eaghe GdfXGe GdbGfhfi cfehPL JMdjdi ddacQI GdQSejI ddbGfhf ceG MOOJgG GdeGOI GdKGfjI ef GdOSJhQ; h Pdc dQHW Jdc GdacQI GdQSejI ddbGfhf HLPhQgG GdadSajI GdYejbI(B: (3h UjGZI fSbkG adSajkG eJcGedkG HLhGfHg GdKdGKI(B: (3GdGfWhdhLi(B: (3GdGHSJehdhLi(B: (3h GdGcSjhdhLi h eKd cd LGfH ef gPg GdLhGfH GdKdGKI HGHkG ef CHhGH GdQSGdIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe adSaI GdbGfhf h JGQjNg, (B2018s
(3HHdjhLQGajG(B: (3UaMGJ (B336-371s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3adSaI GdbGfhf hJGQjNIs; (3GdLGfH GdGfWhdhLj ddfXGe GdbGfhfj GdeUQjs; (3GdfXGe GdbGfhfis; (3GdeYJRdIs; (3GdeGJQjOjs; (3GdGTGYQIs; (3GdeOGQS GdcdGejIs; (3GLGfH GdGHJSehdhLj s; (3GdLGfH GdGcSjhdhLj Gdbjejs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3adSaI GdbGfhf hJGQjNIs